2012
DOI: 10.1007/s10549-012-2175-5
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin E inhibits breast tumor metastasis by suppressing cell migration and invasion

Abstract: Tumor metastasis is the main cause of cancer-related deaths of patients. Breast cancer is highly malignant with considerable metastatic potential, which urges the necessity for developing novel potential drug candidate to prevent tumor metastasis. Here, we report our finding with Cucurbitacin E (CuE, α-elaterin), a tetracyclic triterpenes compound isolated from Cucurbitaceae. The potency of CuE on breast cancer metastasis inhibition was assessed in vivo and in vitro. In our animal experiments, intraperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 48 publications
0
86
0
Order By: Relevance
“…The unanticipated finding that cucurbitacin I activates RhoA in breast cancer cells led us to speculate that the inhibitory effect of this compound on Rac1 activation could be related to an imbalance between the activity of Rac and Rho. Cucurbitacin I and its derivatives are natural terpenoids isolated from plants that have been extensively studied due to their anticancer and anti-inflammatory activities (Chen et al, 2005;Iwanski et al, 2010;Lee et al, 2010), and more recently identified as potent antimetastatic agents in breast cancer (Zhang et al, 2012a) Cucurbitacin B treatment of cancer cells, including breast Tannin-Spitz et al, 2007;Wakimoto et al, 2008;Dakeng et al, 2012). In fact, numerous reports show that cucurbitacin derivatives induce cell cycle arrest, mainly in G 2 /M.…”
Section: Discussionmentioning
confidence: 99%
“…The unanticipated finding that cucurbitacin I activates RhoA in breast cancer cells led us to speculate that the inhibitory effect of this compound on Rac1 activation could be related to an imbalance between the activity of Rac and Rho. Cucurbitacin I and its derivatives are natural terpenoids isolated from plants that have been extensively studied due to their anticancer and anti-inflammatory activities (Chen et al, 2005;Iwanski et al, 2010;Lee et al, 2010), and more recently identified as potent antimetastatic agents in breast cancer (Zhang et al, 2012a) Cucurbitacin B treatment of cancer cells, including breast Tannin-Spitz et al, 2007;Wakimoto et al, 2008;Dakeng et al, 2012). In fact, numerous reports show that cucurbitacin derivatives induce cell cycle arrest, mainly in G 2 /M.…”
Section: Discussionmentioning
confidence: 99%
“…In MDA-MB-231 and 4T1 human breast cancer cells, cucurbitacin E suppresses breast tumor metastasis via inhibition of the Src/FAK/Rac1/MMP pathway (103). In PC3 and HUVEC cells, cucurbitacin E restrains tumor angiogenesis via inhibition of VEGFR2-mediated Jak/ STAT3 and MAPK signaling pathways (104).…”
Section: Steroidmentioning
confidence: 99%
“…And its poor prognosis is always related to invasion and metastasis, which are typical features for breast cancer patients in their advanced tumor progression [2,3]. In a typical metastasis process, tumor cells have to disseminate and intravasate into blood vessels at the primary tumor site, travel through the vascular systems, and then extravasate out from blood vessel to colonialize in the parenchyma of distal tissues.…”
Section: Introductionmentioning
confidence: 99%